Intermittent Theta-Burst Transcranial Magnetic Stimulation Alters Electrical Properties of Fast-Spiking Neocortical Interneurons in an Age-Dependent Fashion - Hoppenrath, Kathrin; Härtig, Wolfgang; Funke, Klaus (Frontiers in Neural Circuits, 2016)
Modulation of human cortical excitability by repetitive transcranial magnetic stimulation (rTMS) appears to be in part related to changed activity of inhibitory systems. Our own studies showed that intermittent theta-burst stimulation (iTBS) applied via rTMS to rat cortex primarily affects the parvalbumin-expressing (PV) fast-spiking interneurons (FSIs), evident via a strongly reduced PV expression. We further found the iTBS effect on PV to be age-dependent since no reduction in PV could be induced before the perineuronal nets (PNNs) of FSIs start to grow around postnatal day 30. To elucidate possible iTBS-induced changes in the electrical properties of FSIs and cortical network activity during cortical critical period, we performed ex vivo – in vitro whole-cell patch clamp recordings from pre-labelled FSIs in the current study. FSIs of verum iTBS-treated rats displayed a higher excitability than sham-treated controls at PD29-38, evident as higher rates of induced action potential firing at low current injections (100-200 pA) and a more depolarized resting membrane potential. This effect was absent in younger (PD26-28) and older animals (PD40-62). Slices of verum iTBS-treated rats further showed higher rates of spontaneous EPSCs. Based on these and previous findings we conclude that FSIs are particularly sensitive to theta-burst stimulation during early cortical development, when FSIs show an activity-driven step of maturation which is paralleled by intense growth of the PNNs and subsequent closure of the cortical critical period. Although to be proven further, rTMS may be a possible early intervention to compensate for hypo-activity related mal-development of cortical neuronal circuits.